Sport and Tourism in Contemporary Society - Blanco Gregory, Rocío; Monaco, Salvatore (Eracle. Journal of Sport and Social Sciences, 2019)
One of the main Urry’s lessons is that the tourist experience, with the advent of postmodernism, have started to contribute more to the formation of the identity of people, thanks to the proliferation of information channels and means of transport that have made possible, in fact, a series of practices and dynamics until a few years ago unimaginable (Urry, 2000; Urry & Sheller, 2004, 2006). Today tourism is set up as a cultural experience that is characterized as a time when people, objects, symbols, images and cultures meet, merge and mutually condition.